Legal and geopolitical complexity in the Arctic : the impact of global crises on regional competition - Melchiorre, Tiziana (Routledge, 2026)
"This book examines the evolving geopolitical landscape of the Arctic, focusing on the impact of climate change and the war in Ukraine on regional and international relations from a legal and geopolitical perspective. As Arctic ice melts, newly accessible natural resources and transportation routes are intensifying territorial and maritime disputes, heightening competition and tensions among regional states. The war in Ukraine has further strained relations between the West and Russia, disrupting political, economic, and scientific cooperation while accelerating the militarization of the Arctic. In response to Russia's aggressive actions in Eastern Europe, Western states have expanded their military presence in the region, while Russia has modernized its Arctic military infrastructure. Through analysing these developments, the book highlights the interconnection between regional and global dynamics. It argues that climate change and geopolitical conflict are transforming the Arctic from the "last frontier" into the "first frontier"; a strategic arena where states, both within and beyond the region, seek to assert their geopolitical and economic interests. Adopting an interdisciplinary approach that integrates international relations, international law, and history, this book provides a comprehensive examination of the Arctic's legal and geopolitical complexities. The book will be of interest to researchers in the field of international relations and public international law, as well as environmental and Arctic law"-- Provided by publisher.
Keywords: Law -- Arctic regions.; Climatic changes -- Law and legislation -- Arctic regions.; Environmental law -- Arctic regions.; Natural resources -- Law and legislation -- Arctic regions.; Russian Invasion of Ukraine, 2022.; Geopolitics -- Arctic regions.; Arctic regions -- International status.; elektronické knihy; electronic books